Calibration of Managerial Resilience Strategies in Anticipating Global Supply Chain Disruptions within Export-Oriented Manufacturing Firms - Liana, Lani (CV. HEI PUBLISHING INDONESIA, 2024)
The global export manufacturing landscape is currently navigating a state of